2021
DOI: 10.4208/cicp.oa-2020-0152
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Water Moment Models for Bedload Transport Problems

Abstract: In this work a simple but accurate shallow model for bedload sediment transport is proposed. The model is based on applying the moment approach to the Shallow Water Exner model, making it possible to recover the vertical structure of the flow. This approach allows us to obtain a better approximation of the fluid velocity close to the bottom, which is the relevant velocity for the sediment transport. A general Shallow Water Exner moment model allowing for polynomial velocity profiles of arbitrary order is obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It was shown that the HSWME yield accurate results while preserving hyperbolicity of the model equations [29]. Recently, the model has been applied to sediment transport [17] and analysis of steady states and equilibrium stability has been performed [21,28].…”
Section: Hyperbolic Shallow Water Moment Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the HSWME yield accurate results while preserving hyperbolicity of the model equations [29]. Recently, the model has been applied to sediment transport [17] and analysis of steady states and equilibrium stability has been performed [21,28].…”
Section: Hyperbolic Shallow Water Moment Equationsmentioning
confidence: 99%
“…The model is based on a hyperbolic regularization of [32] using techniques from kinetic theory [15,30]. The increased accuracy of the model was shown in numerical simulations, including sediment transport [17]. However, the HSWME also lead to a higher computational cost and memory footprint due to additional nonlinear equations for the expansion coefficients of the polynomial velocity profile.…”
Section: Introductionmentioning
confidence: 99%